The Tradition of Capture Marriage in Sumba: A Review from the Perspective of Indonesian Positive Law - Elaies, Ranissa Sekar (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study examines the practice of capture marriage in Southwest Sumba, Indonesia, with a focus on how this traditional custom has evolved into a violation of women’s rights. Historically, this practice involved mutual consent between families; however, recent cases demonstrate its transformation into acts of forced marriage and violence against women. The research utilizes a normative methodology, analyzing the tradition through the lens of Indonesian positive law, including Marriage Law No. 16 of 2019, Sexual Violence Crimes Law No. 12 of 2022, and Human Rights Law No. 39 of 1999. The study reveals that current instances of capture marriage often involve criminal elements such as physical violence, verbal abuse, and sexual assault. Although Article 18B of the 1945 Constitution recognizes customary laws, such practices must be consistent with societal development and state principles. The study concludes that capture marriage, in its present form, should be eradicated as it violates women’s rights and contradicts contemporary legal frameworks.